Sustainability Reporting Terhadap Nilai Perusahaan: Dengan Knerja Keuangan Sebagai Variabel Intervening Pada Perusahaan Non Keuangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2016 – 2019 - Putri Sholikhah; Hidayatul Khusnah (Universitas Nahdlatul Ulama Surabaya, 2020)
This study aims to test Sustainability Reporting on Firm Value: with Financial Performance as an Intervening Variable. The independent variable in this study is Sustainability Reporting, the dependent variable in this study is Firm Value, and Financial Performance as an intervening variable. This study uses secondary data, namely data obtained from annual financial reports and sustainability reports on non-financial companies listed on the IDX from 2016 to 2019. The sample used in this study was 11 companies. Using purposive sampling research method and the application program WarpPLS 6.0 was used in the data analysis process. The results showed that Sustainability Reporting with economic, environmental, and social indicators showed only economic and environmental indicators that had a positive and significant effect on financial performance, while social indicators had no effect on financial performance. Economic and environmental indicators have a positive and significant effect on firm value, while social indicators have a negative and significant effect on firm value. Financial performance with the ROA indicator has a positive and significant effect on Tobins'Q. Financial performance can reconcile the sustainability report with economic and environmental indicators related to company value. However, financial performance cannot mediate the relationship between social indicators and firm value.